Managing Learning Skills to Improve the Learning Quality of Children with Mild Intellectual Disability SLB Sukagalih and SLB ABC YPLAB Lembang, West Bandung Regency, West Java - Mastiani, Emay; Mulyasana, Dedi (Angstrom Centre of Education, 2022)
This study focused on managing learning skills to improve the learning quality of children with mild intellectual disability SLB Sukagalih and SLB ABC YPLAB Lembang, West Bandung Regency, West Java. Vocational learning programs for mild intellectual disability in special high school education units have not been properly managed to meet employment demands. The mismanagement is mainly caused by several factors, including the teachers' skillset that is not suitable for the skills needed in the field, the inadequate facilities and infrastructure, and the management of skills learning has not been carried out as needed. This study aims to determine what management of skills learning will likely improve its quality for children with mild intellectual disability at special needs schools so that the graduates can be accepted in the work field. Data collection was conducted through observation, interviews, and documentation study. The results showed that: 1) the work skills type selection given to students is not entirely based on the work fields’ requirement but rather more often refers to the skills mastered by the teacher, 2) work skills learning implementation has been carried out starting from planning, implementation, evaluation, and follow-up. 3) the obstacles schools and teachers face in implementing skills learning are no available assessment for various work skill types, the children who lack confidence, and lack of trust from the community about their employability. 4) Improvement efforts made by schools and teachers are choosing the skill types suitable to the work field, increasing the teacher's ability to master work-related skills, and establishing cooperation with the job providers. Recommends school and teacher to improve the collaboration with the job providers and make written agreements for both parties to provide a legal foundation in conduct cooperation.